A Comparison of Dental Caries Levels in Two Communities with Different Oral Health Prevention Strategies Stratified in Different Social Classes - Darius Sagheri, PhD; Jacinta McLoughlin, MDS; John J. Clarkson, PhD (Blackwell Synergy, 2007)
To compare dental caries levels of schoolchildren stratified in different social classes whose domestic water supply had been fluoridated since birth (Dublin) with those living in an area where fluoridated salt was available (Freiburg).